2016
DOI: 10.1016/j.wocn.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the lexical distribution and implementation of phonetically similar phonemes in Catalan

Abstract: A B S T R A C TIn some Romance languages with two pairs of mid vowel phonemes, it is acknowledged that these contrasts are somewhat unstable. We analyze the distribution and realization of the anterior and posterior mid vowels in Catalan to test claims (mostly based on anecdotal evidence) that these contrasts exhibit inter-and intraspeaker variability. Participants produced target words containing stressed mid vowels and, later, judged vowel height (/e/ vs. /ɛ/; /o/ vs. /ɔ/) in the same words. The results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 46 publications
3
22
0
Order By: Relevance
“…In contrast, we elicited our data in a cued picture naming task in the present study, in which the participants needed to activate isolated lexical representations. Moreover, the lack of contrast observed here could have been caused by the selection of different lexical items, a factor that has previously been shown to be critical for Catalan mid-vowels (Nadeu & Renwick, 2016). However, despite some variation in the items used across the studies, all three contain highly similar materials, with bisyllabic words used in virtually all instances.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In contrast, we elicited our data in a cued picture naming task in the present study, in which the participants needed to activate isolated lexical representations. Moreover, the lack of contrast observed here could have been caused by the selection of different lexical items, a factor that has previously been shown to be critical for Catalan mid-vowels (Nadeu & Renwick, 2016). However, despite some variation in the items used across the studies, all three contain highly similar materials, with bisyllabic words used in virtually all instances.…”
Section: Discussionmentioning
confidence: 66%
“…/e-ɛ/ and /o-ɔ/ (Regueira, 1996), while Spanish only distinguishes a single mid front and mid back vowel. Previous work from Galician and other Romance languages, has shown that these contrasts are particularly difficult to acquire and maintain (Amengual, 2016;Amengual & Chamorro, 2015;Mora, Keidel & Flege, 2015;Mora & Nadeu, 2012;Nadeu & Renwick, 2016;Pallier, Bosch & Sebastián-Gallés, 1997;Renwick & Ladd, 2016;Renwick & Nadeu, 2018;Tomé Lourido & Evans, 2015Simonet, 2011). This instability has not only been documented in bilingual settings where acquisition and maintenance may be adversely affected by interaction with a language that lacks mid vowel contrasts, as in the case of Galician and Catalan, but also in monolingual settings.…”
Section: Mid Vowel Contrasts and The Galician Contextmentioning
confidence: 99%
“…To the extent that they hear a mixture of regional varieties in their daily lives (e.g., in large cities and via national broadcast media), many speakers will have the experience of ignoring mid vowel quality in making lexical identifications during normal speech comprehension. Although the limited functional load of the phonetic distinction and the general redundancy of the speech signal ensure that misunderstandings will almost never arise, this variation could contribute to a weakening of their phonological representations and intuitions, as has recently been suggested for Catalan (Nadeu & Renwick, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our aim, then, is not to investigate questions of dialectology or sociolinguistics, but to see whether there are generalizations to be drawn about the manifestations of phonological closeness in the behavior of individual speakers, regardless of where they come from. The heart of our methodology is to link individual speakers' pronunciations to their own judgments of mid vowel height, a technique also used for Catalan mid vowels by Nadeu and Renwick (2016). Our specific research questions included the following:…”
Section: Italian Mid Vowelsmentioning
confidence: 99%
“…Increasingly, however, close analysis of the relationships among sounds has revealed gradient, even marginal, phonological contrasts. Evidence comes from speech production [1,2,3], speech perception [4,5] and via sounds' distribution in the language, particularly functional load [6,7]. Functional load is estimated with measures that consider how languages use particular contrasts, i.e.…”
Section: Introductionmentioning
confidence: 99%